Peranan Filsafat Ilmu Terhadap Manajemen Lingkungan - Fahmiaty Ilmiah (Prodi Ilmu Administrasi Negara, 2016)
The objective of this research will know the influence of the philosophy of science towards the environment. The location of the research is in Samarinda in 2014. The method of it is qualitative one. The results of it are (1). The definition of the philosophy of science is the combined study which consists some performance to define the strict limit about a defined study and the definition of The environment management also the aspects to all the functions of management which defines and bring the implementation of environment policy (BBS 7750, in ISO 14001 by Sturm,1998). (2). To give a Management system to be grown to give the basic guidance which is always within the philosophy science in order to the business is always closed with environment, (3). The factor of the role between philosophy science and environment management and others as well. The suggestions of this research as follows, (1). It is badly needed to deepen the study about philosophy science and environment management that it cannot be taken away concerning environment management (2). It must be enlarged about the role philosophy of science in the environment management because the factors of the role of philosophy science not only limited in the research and other scientific study only. (3). The definition of the philosophy science must be briefly because there are many others.